Bridging the Employment Gap: Analyzing the Implementation of Padang City’s Workforce Placement Program - Herman Putri, Adhinda; Ichsan Kabullah, Muhammad; Wahyuni, Nila (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
This research examines the implementation of the Manpower Placement Program in Padang City, West Sumatra, addressing the city's high unemployment rate. Employing a qualitative approach with descriptive methods, the study utilizes documentation and interviews with key informants from the Manpower and Industry Office, employers, and private placement agencies. The study reveals suboptimal program implementation, with objectives not fully achieved despite a decreased open unemployment rate. Padang City still faces the highest unemployment rate in West Sumatra, with a significant disparity between registered and placed job seekers. Challenges identified include inadequate human and non-human resources within the Manpower and Industry Office, suboptimal communication and coordination between implementers and external organizations, a mismatch between job seeker competencies and employer demands, and insufficient support from political elites and local regulations. The research emphasizes the need to develop localized policy frameworks that address Padang's unique socio-economic conditions, implement innovative resource strategies, enhance coordination mechanisms, and adopt context-sensitive approaches to balance national directives with local realities. These recommendations aim to improve the program's effectiveness and align it with the city's needs and challenges. This study's critical implication is that ineffective policy implementation highlights the need for a comprehensive, localized approach to address critical issues, considering the city's unique socio-economic conditions and resource constraints.